The Jewish century - Slëzkin, Jurij Lʹvovič 1956- (Princeton Univ. Press, 2004)
The author claims that not only have Jews adapted better than many other groups to living in the modern world, they have become the premiere symbol and standard of modern life everywhere. The Jews traditionally belonged to a social category known as "service nomads," an outsider group specializing in the delivery of goods and services. This role--urban, mobile, literate, articulate, intellectually intricate, physically fastidious, and occupationally flexible--has taken center stage in the modern age. Marxism and Freudianism sprang largely from the Jewish predicament, and both Soviet Bolshevism and American liberalism were affected in fundamental ways by the Jewish exodus from the Pale of Settlement. The book concentrates on the drama of the Russian Jews, including §migr¿Ł and their offspring in America, Palestine, and the Soviet Union. But Slezkine has as much to say about the many faces of modernity as he does about Jewry.--Publisher